Effect of Grit Chamber Configuration on Particle Removal: Using Response Surface Method - Esfahani, Nikoo Roghani; Mobarekeh, Mohsen Nourouzi; Hoodaji, Mehran (Journal of Membrane and Separation Technology, 2018)
In recent years ever-increasing industrial growth has resulted in a significant increase in the production of wastewater, this wastewater sometimes contains high levels of suspended solids. Therefore, the need to formulate an appropriate course of action for managing this wastewater has reached a critical level. In this study, the removal of suspended particles in wastewater that were a byproduct of an idustrial cut stone production process were investigated. For these purposes, a laboratory grit chamber was employed, and response surface methodology (RSM) was used to simulate the contributing parameters in the settling process. In order to study the performance of the grit chamber, factors such as flow rate, inlet location and mesh size, parameters of pH, COD, BOD, TSS and turbidity in influent and effluent were monitored. Results indicated that values of pH, COD and BOD in raw wastewater were within the standard range of discharging wastewater. The results indicated that the model with a high correlation of 0.95 was able to simulate the process. In addition, turbidity removal was found to be affected by three parameters among which mesh size and its interaction with the flow rate were the most influential ones.